Education plus exercise versus corticosteroid injection use versus a wait and see approach on global outcome and pain from gluteal tendinopathy: prospective, single blinded, randomised clinical trial - Mellor, R; Bennell, K; Grimaldi, A; Nicolson, P; Kasza, J; Hodges, P; Wajswelner, H; Vicenzino, B (BMJ Publishing Group, 2018)
Objective To compare the effects of a programme of load management education plus exercise, corticosteroid injection use, and no treatment on pain and global improvement in individuals with gluteal tendinopathy. Design Prospective, three arm, single blinded, randomised clinical trial. Setting Brisbane and Melbourne, Australia. Participants Individuals aged 35–70 years, with lateral hip pain for more than 3 months, at least 4/10 on the pain numerical rating scale, and gluteal tendinopathy confirmed by clinical diagnosis and MRI; and with no corticosteroid injection use in previous 12 months, current physiotherapy, total hip replacement, or neurological conditions. Interventions A physiotherapy led education and exercise programme of 14 sessions over 8 weeks (EDX; n=69), one corticosteroid injection (CSI; n=66), and a wait and see approach (WS; n=69). Main outcomes Primary outcomes were patient reported global rating of change in hip condition (on an 11 point scale, dichotomised to success and non-success) and pain intensity in the past week (0=no pain, 10=worst pain) at 8 weeks, with longer term follow-up at 52 weeks. Results Of 204 randomised participants (including 167 women; mean age 54.8 years (SD 8.8)), 189 (92.6%) completed 52 week follow-up. Success on the global rating of change was reported at 8 weeks by 51/66 EDX, 38/65 CSI, and 20/68 WS participants. EDX and CSI had better global improvement scores than WS (risk difference 49.1% (95% CI 34.6% to 63.5%), number needed to treat 2.0 (95% CI 1.6 to 2.9); 29.2% (13.2% to 45.2%), 3.4 (2.2 to 7.6); respectively). EDX had better global improvement scores than CSI (19.9% (4.7% to 35.0%); 5.0 (2.9 to 21.1)). At 8 weeks, reported pain on the numerical rating scale was mean score 1.5 (SD 1.5) for EDX, 2.7 (2.4) for CSI, and 3.8 (2.0) for WS. EDX and CSI participants reported less pain than WS (mean difference −2.2 (95% CI −2.89 to −1.54); −1.2 (−1.85 to −0.50); respectively), and EDX participants reported less pain than CSI (−1.04 (−1.72 to −0.37)). Success on the global rating of change was reported at 52 weeks by 51/65 EDX, 36/63 CSI, and 31/60 WS participants; EDX was better than CSI (20.4% (4.9% to 35.9%); 4.9 (2.8 to 20.6)) and WS (26.8% (11.3% to 42.3%); 3.7 (2.4 to 8.8)). Reported pain at 52 weeks was 2.1 (2.2) for EDX, 2.3 (1.9) for CSI, and 3.2 (2.6) for WS; EDX did not differ from CSI (−0.26 (−1.06 to 0.55)), but both treatments did better than WS (1.13 (−1.93 to −0.33); 0.87 (−1.68 to −0.07); respectively). Conclusions For gluteal tendinopathy, education plus exercise and corticosteroid injection use resulted in higher rates of patient reported global improvement and lower pain intensity than no treatment at eight weeks. Education plus exercise performed better than corticosteroid injection use. At 52 week follow-up, education plus exercise led to better global improvement than corticosteroid injection use, but no difference in pain intensity. These results support EDX as an effective management approach for gluteal tendinopathy.